Theatre and Migration in Gilgamesh - Worthington, Martin (Palgrave, 2023)
Gilgamesh is not a play, and it does not explicitly deal with migration in the sense of ‘movements by groups’ (indeed, it is generally less concerned with groups than with individuals). And yet, ‘theatre’ and ‘migration’ are, both singly and conjointly, useful lenses through which to view this ancient Babylonian narrative. I will therefore deal with the two themes in turn, then discuss their interrelations in a specific performance. Gilgamesh was a legendary king of Uruk, about whom several poems existed in both Sumerian and Babylonian. They are known from manuscripts (clay tablets) from c. 1800 BC onwards (the stories in Sumerian are suspected to be older). This paper concentrates on the ‘Standard Version’ of the Babylonian poem, which is the best-preserved and most widely known. The date of redaction of the Standard Version is unknown, but the manuscripts date to the first millennium BC. By far the best and fullest edition is that of Andrew George (2003), which includes extensive and authoritative introductory matter. The poem comprised c. 3000 lines, of which 2000+ are currently known. It is divided into eleven chapters or cantos, each of which was written on a single clay tablet. The chapters are therefore also known as ‘Tablets,’ and are referred to with Roman numbers. There is further a twelfth Tablet (not treated here), which is prose rather than poetry, and which contradicts the main plot. The essentials of the story are these: Gilgamesh’s rule is overbearing, so the people of Uruk complain to the gods. These send a purpose-made creature, Enkidu, to calm Gilgamesh down. After first living Mowgli-like with gazelles, Enkidu is humanised by the prostitute Shamhat, and becomes Gilgamesh’s bosom friend. Together they mount an expedition to the Cedar Forest, killing its guardian Humbaba. Then they kill the Bull of Heaven, sent by Ishtar, goddess of sex and war, because Gilgamesh refuses her offer of marriage. The gods are angered, and Enkidu must die. In despair, Gilgamesh goes in search of immortality, journeying to the faraway Babylonian Noah (Uta-napishti), encountering magical beings along the way. But Uta-napishti explains that he became immortal because of the Flood, and the circumstances cannot be replicated. Hence, in Tablet XI, Gilgamesh returns to Uruk unsuccessful but, it is implied, wiser. (In the prose Tablet XII, Enkidu is still alive). Translations differ widely both in accuracy and in faithfulness to the original Babylonian. Moreover, as new fragments of tablets are found, translations need updating. At the present time, George (2003) or his volume in Penguin Classics can be particularly recommended.
Palgrave Handbook on Theatre and Migration
PUBLISHED
Keywords: Creative Arts Practice; Manuscript, Book and Print Cultures; Assyriology; Drama, Theatre and Performance; Folklore and Mythology; Language and/or Literature, Fiction; Performance Arts